Effect of an executive function cognitive training program on the planning component in adults with mild intellectual disability - Acosta Echavarría, Álvaro Alejandro; Montoya Arenas , David Andrés; Landinez , Daniel; González Uribe , Ana María; Gómez Tabares, Anyerson Stiths; Acosta Echavarría, Álvaro Alejandro; Montoya Arenas , David Andrés; Landinez , Daniel; González Uribe , Ana María; Gómez Tabares, Anyerson Stiths; Acosta Echavarría, Álvaro Alejandro; Montoya Arenas , David Andrés; et al. (Corporación Universitaria Americana, 2024)
Introduction: Disability today is represented in approximately 1 billion people worldwide, whose condition generates limitations that encompass functional, adaptive and cognitive. Objective: to evaluate the effect of a computerized cognitive training program on the executive function of planning in people with mild intellectual disability. Methodology: A quasi-experimental design was used with 10 participants, who received 20 training sessions for 2 months. Planning skills were evaluated before and after the program. Results: Significant improvements in planning skills were evidenced after the training. Participants were able to complete the maze and king figure tasks in less time, indicating greater efficiency in problem solving. These findings support the effectiveness of computerized cognitive training in improving cognitive performance in people with mild intellectual disability. Conclusions: These results are relevant in the field of neuropsychology, as they demonstrate that computerized programs can have a positive impact on the development of executive functions in this population. In addition, they highlight the importance of using interactive and technological approaches in psychopedagogical and neuropsychological interventions.